2020
DOI: 10.1007/s00520-020-05592-w
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial on the efficacy of life review therapy targeting incurably ill cancer patients: do their informal caregivers benefit?

Abstract: Purpose Investigate whether Life Review Therapy and Memory Specificity Training (LRT-MST) targeting incurably ill cancer patients may also have a beneficial effect on caregiving burden, symptoms of anxiety and depression, and posttraumatic growth of the informal caregivers. Methods Data was collected in the context of a randomized controlled trial (RCT) (secondary analyses) on the effect of LRT-MST among incurably cancer patients. Informal caregivers of participating patients were asked to complete outcome mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Of the 49 included trials, 34 (69%) included caregivers of patients with mixed solid tumor malignancies, 6 (12%) only lung cancer ( 42 , 59-62 , 69 , 72 , 81 ), 1 (2%) breast cancer ( 74 ), 1 (2%) pancreatic cancer ( 94 ), 1 (2%) high-grade glioma ( 43 ), 2 (4%) gastrointestinal cancers ( 73 , 76 ), and 4 (8%) hematological malignancies ( 44 , 49 , 80 , 84 ). A total of 32 (65%) trials were conducted in an outpatient setting ( 42-45 , 53-57 , 59-77 , 81-83 , 85 , 87 , 88 , 91 , 92 , 94 ), 5 (10%) in a home setting ( 46-48 , 51 , 78 , 79 , 86 ), 4 (8%) in an inpatient setting ( 41 , 80 , 84 , 96 ), and 8 (16%) in mixed settings ( 49 , 50 , 52 , 58 , 89 , 90 , 93 , 95 ). Of the trials, 28 were conducted in the United States ( 44 , 45 , 49-51 , 53 , 55 , 59-68 , 71-77 , 83-86 , 89 , 92 , 94 , 95 ); 4 each in Australia ( 46-48 , 52 , …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 49 included trials, 34 (69%) included caregivers of patients with mixed solid tumor malignancies, 6 (12%) only lung cancer ( 42 , 59-62 , 69 , 72 , 81 ), 1 (2%) breast cancer ( 74 ), 1 (2%) pancreatic cancer ( 94 ), 1 (2%) high-grade glioma ( 43 ), 2 (4%) gastrointestinal cancers ( 73 , 76 ), and 4 (8%) hematological malignancies ( 44 , 49 , 80 , 84 ). A total of 32 (65%) trials were conducted in an outpatient setting ( 42-45 , 53-57 , 59-77 , 81-83 , 85 , 87 , 88 , 91 , 92 , 94 ), 5 (10%) in a home setting ( 46-48 , 51 , 78 , 79 , 86 ), 4 (8%) in an inpatient setting ( 41 , 80 , 84 , 96 ), and 8 (16%) in mixed settings ( 49 , 50 , 52 , 58 , 89 , 90 , 93 , 95 ). Of the trials, 28 were conducted in the United States ( 44 , 45 , 49-51 , 53 , 55 , 59-68 , 71-77 , 83-86 , 89 , 92 , 94 , 95 ); 4 each in Australia ( 46-48 , 52 , …”
Section: Resultsmentioning
confidence: 99%
“…A total of 32 (65%) trials were conducted in an outpatient setting ( 42-45 , 53-57 , 59-77 , 81-83 , 85 , 87 , 88 , 91 , 92 , 94 ), 5 (10%) in a home setting ( 46-48 , 51 , 78 , 79 , 86 ), 4 (8%) in an inpatient setting ( 41 , 80 , 84 , 96 ), and 8 (16%) in mixed settings ( 49 , 50 , 52 , 58 , 89 , 90 , 93 , 95 ). Of the trials, 28 were conducted in the United States ( 44 , 45 , 49-51 , 53 , 55 , 59-68 , 71-77 , 83-86 , 89 , 92 , 94 , 95 ); 4 each in Australia ( 46-48 , 52 , 87 , 88 ) and China ( 69 , 80 , 81 , 96 ); 3 in Canada ( 42 , 70 , 91 ); 2 each in the United Kingdom ( 54 , 82 ), Netherlands ( 43 , 90 ), and Denmark ( 58 , 78 , 79 ); and 1 each in Colombia ( 41 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, reminiscence therapy combined with memory speci c training is mainly used in the psychological treatment of cancer patients in palliative care, and its effectiveness needs further validation, as randomized controlled trials Life Review Therapy combined with Memory Speci city Training (LRT-MST) by Gitta Kleijn showed that no signi cant differences were found between the two groups for anxiety, depression, quality of life and autobiographical memory in cancer patients (38,39). however, other studies have shown that reminiscence therapy based on autobiographical memory training can be used in future studies to investigate available, cost-effective, low-intensity treatment options for patients experiencing mood disorders (40,41), and therefore further investigation of this therapy is warranted.…”
Section: Introductionmentioning
confidence: 99%